Recuperação de compostos bioativos de resíduos oriundos do processamento de óleos vegetais por meio da aplicação do processo combinado de esterificação-destilação molecular - Silva, Maurício Dalla Costa Rodrigues da (2023)
The vegetable oil refining process generates residues that can be reused to recover compounds with high-added value. The deodorized distillates are a source for the recovery of vitamin E, phytosterols, and squalene. Among the operations used in the recovery of these compounds, molecular distillation stands out due to the lower degradation of bioactive compounds. However, preliminary steps of chemical modification of some components must be carried out to improve the separation process. In this sense, the work proposed here aimed to study the recovery of compounds with a high-added value from deodorized distillates through the application of the combined process of esterification-molecular distillation. Additionally, the study presented here aimed at valuing this type of residue, evaluating variations in phytonutrient content throughout the esterification stages and the improvements obtained in the molecular distillation process as a function of esterification. The deodorized distillates used in this study come from semi-continuous (DD) and continuous (PFAD) deodorization processes. The determination of best conditions to carry out the esterification of free fatty acids present in the residues were determined using rotational central composite design (DCCR), taking into account the conversion of free fatty acids and the amount of phytonutrients at the end of the reaction. The best conditions to conduct DD esterification were 3% m m-1 H2SO4, 2:1 methanol-free fatty acid molar ratio, and 214 min. For the PFAD, the best conditions were 2% m m-1 of H2SO4, 10:1 methanol-free fatty acids molar ratio, and 213 min. In both residues, it was possible to obtain conditions that aligned the higher conversion of free fatty acids (90% for DD and 98% for PFAD) with a lower loss of evaluated phytonutrients (approximately 3% for both residues). Furthermore, the experimental validation showed that the results obtained showed good reproducibility. Performing esterification substantially improved the separation of phytonutrients by molecular distillation, with pronounced increases in enrichment factors (145-939%) being obtained in the residue streams for the evaluated phytonutrients. Thus, based on the results obtained, it is concluded that the combination esterification-molecular distillation is a promising route for the recovery of compounds with high added value from residues arising from the deodorization of vegetable oils.